The International Comparison and Trend Analysis of the Development of MOOCs in Higher Education - Zheng, Qinhua; Li, Chen; Burgos, Daniel (Lecture Notes in Educational Technology, 2020)
This chapter explores the potential impact of Massive Open Online Courses (MOOCs) on the international aspects of university development, claiming that the development and offering of MOOCs can affect not only universities’ educational offerings but also the way they plan their development within an increasingly globalized context. This chapter argues that MOOCs can contribute to enhancing universities’ international cooperation and propose six patterns of international cooperation among universities empowered by MOOCs.
Capítulo del libro "Zheng Q., Chen L., Burgos D. (2018) The Development of MOOCs in China. Lecture Notes in Educational Technology. Springer, Singapore".
Keywords: Scopus(2); WOS(2)